Strategi Marketing Syari’ah Dalam Meningkatkan Pendapatan Pada Jasmine Home Spa Khusus Wanita Cabang Cirebon - Dapiah Dapiah; Nurhayati Nurhayati; Siti Khumaeroh (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2020)
Jasmine Home Spa is one of the companies engaged in spa services for women, such as massage, body scrub, facials, full-blooded face and others. One of the plus points of Jasmine Spa is that this spa is exclusively for women and the price is affordable so that it can be enjoyed by the middle class. The purpose of writing this journal is to analyze the extent of Jasmine home Spa in implementing Sharia Marketing as an effort to increase revenue. The type of method used is a qualitative method. By interviewing Jasmine home Spa informants and field research procedures that produce descriptive data, in order to obtain results in the form of images, benefits and application of meaningful knowledge in depth. From the results of the study, Jasmine home Spa in its efforts to run Islamic principles by instilling Islamic values ​​both in the work culture of its employees and marketing strategies. Judging from the perspective of the sharia marketing strategy, Jasmine home Spa applies an Islamic marketing strategy consisting of applying the characteristics of Islamic marketing, applying Islamic business ethics, and following the marketing practices of the Prophet Muhammad SAW Abstrak Jasmine Home Spa merupakan salah satu perusahaan yang bergerak di bidang jasa pelayanan spa khusus wanita, seperti massage,lulur, facial, totok wajah dan lain-lain. Salah satu nilai plus yang dimiliki jasmine Spa ialah spa ini khusus wanita serta harganya yang terjangkau sehingga bisa dinikmati kalangan menengah. Tujuan dari penulisan jurnal ini adalah untuk menganalisis sejauhmana Jasmine home Spa dalam melaksanakan Marketing syariah sebagai upayanya dalam meningkatkan pendapatan. Jenis metode yang digunakan adalah metode kualitatif. Dengan cara mewawancarai informan Jasmine home Spa dan prosedur penelitian lapangan yang menghasilkan data deskriptif, sehingga diperoleh hasil berupa gambaran, manfaat dan penerapan ilmu yang bermakna secara mendalam. Dari hasil penelitian, Jasmine home Spa dalam usahanya menjalankan prinsip-prinsip Islam dengan menanamkan nilai Islam baik dalam budaya kerja karyawannya maupun strategi marketingnya. Di ditinjau dari perspektif strategi marketing syariah, Jasmine home Spa menerapkan strategi pemasaran Islam yang terdiri dari penerapan karakteristik pemasaran Islam, penerapan etika bisnis Islam, dan mengikuti praktik pemasaran Nabi Muhammad SAW.